Bibliometric Analysis of Digital Transformation in MSME Entrepreneurship in the Era of Creative Economy - Judijanto, Loso; Arfiansyah , Ferry; Rusdianto, Rusdianto; Fatchuroji , Acep; Syaiful , Muhammad (West Science Interdisciplinary Studies, 2025)
Digital transformation has become a pivotal driver of innovation and competitiveness in micro, small, and medium enterprises (MSMEs), particularly within the creative economy. This study conducts a bibliometric analysis using Scopus as the primary data source and VOSviewer for visualization to examine the intellectual landscape of digital transformation in MSME entrepreneurship. The findings reveal that entrepreneurship, digital economy, and digital transformation are the dominant research themes, with emerging interest in sustainability, artificial intelligence, and platform-based business models. The temporal analysis highlights a shift from early studies on digital adoption and entrepreneurship education toward more recent discussions on economic development, sustainability, and innovation-driven digital ecosystems. The co-authorship and country collaboration networks indicate strong research connections among the United States, China, India, and Russia, but also reveal gaps in contributions from underrepresented regions. This study identifies key research trends, highlights knowledge gaps, and proposes future research directions, including sustainable digital entrepreneurship, ethical platform governance, and policy frameworks for inclusive digital transformation. The insights provided serve as a foundation for further academic inquiry and strategic policymaking to ensure the equitable and sustainable growth of MSMEs in the digital economy.